Analysis of Difficulties in Applying Polya’s Problem-Solving Method in Solving Physics Problems at SMAN 10 Makassar - A. Rana Aqilah Anwar; Helmi; Usman (Physics Education, 2025)
This study aims to analyze students' difficulties in solving physics problems at SMA Negeri 10 Makassar using Polya's method. Using a descriptive quantitative approach, this research involved 248 twelfth-grade science students, who completed essay tests to assess their abilities in the four stages of Polya’s problem-solving process: understanding the problem, devising a plan, carrying out the plan, and looking back. The results show that in the understanding the problem stage, 28% of students faced high difficulty, mainly in identifying key information. In the devising a plan stage, 44% struggled, especially in selecting appropriate strategies and formulas. In the carrying out the plan stage, 10% encountered difficulties, particularly in calculations. The greatest challenge was in the looking back stage, where 75% of students failed to review their answers, due to a lack of habit in verifying solutions. Overall, the devising a plan and looking back stages were the most challenging. Therefore, more effective learning strategies, such as intensive practice, problem-based learning, and fostering answer verification habits, are needed to enhance students' problem-solving skills in physics.